2017
DOI: 10.5599/jese.374
|View full text |Cite
|
Sign up to set email alerts
|

Deposition efficiency in the preparation of ozone-producing nickel and antimony doped tin oxide anodes

Abstract: The influence of precursor salts in the synthesis of nickel and antimony doped tin oxide (NATO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…To determine if catalyst morphology could explain the trend in selectivity, 13 we characterized the roughness factor using electrochemical capacitance measurements. Capacitance was calculated from CV at variable sweep rates (Equation ). trueC=I()italicdVitalicdt1. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine if catalyst morphology could explain the trend in selectivity, 13 we characterized the roughness factor using electrochemical capacitance measurements. Capacitance was calculated from CV at variable sweep rates (Equation ). trueC=I()italicdVitalicdt1. …”
Section: Resultsmentioning
confidence: 99%
“…Etched substrates were washed and sonicated with Millipore water, dried, and stored under argon until use. A catalyst precursor solution of metal chlorides and nitrates in pure ethanol was prepared based on high performance electrodes of a similar composition by Wang, Christensen, and Sandin 11,13,15 . The precursor mole ratio of (Gd: Ni: Sb: Sn) was ( x : (1‐ x ): 8: 500) where values of x = [1, 0.8, 0.5, 0.2, 0].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…39,42,46,47 However, it is important to note that we observed that if too much SnCl 4 is added to the mixture containing WCl 6 and F-127 in ethanol, this has a deleterious effect by reducing the solubility of F-127 and leads to incomplete dissolution. [48][49][50] To investigate the elemental content of the modified GFs, energy dispersive X-ray spectroscopy (EDX) was used. Figure 4A presents the EDX spectrum of the portion of as-received GF.…”
Section: Physicochemical Characterization Analysismentioning
confidence: 99%